Understanding Millennial Generation Organizational Social Exchange through Psychological Contract - Respati, Yudit Ayu; Rusdiyanto, Wahyu; Yovianingtyas, Clarissa; Tajudin, Anas (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2023)
The rise of the millennial generation, especially in Indonesia, has overtaking the majority of various workplaces. Millennial workers are likely to have different characteristics from the previous generation, so the leader needs to adjust the treatment to create millennials' job satisfaction and engagement. This study aimed to analyze the effect of psychological contracts on work engagement with job satisfaction as a mediating variable. This study used an explanatory method with a quantitative approach. The data was collected using a questionnaire and was analyzed using Partial Least Square software. There were four main findings in the study. First, psychological contracts, both transactional and relational, had a significant effect on job satisfaction. Second, transactional psychological contracts had a significant effect on work engagement. Third, job satisfaction mediated the relationship between transactional and relational psychological contracts with work engagement. Fourth, the rational psychological contract was not the main factor in increasing work engagement.